THE ANISIAN MACROFLORA FROM THE NORTHERN DOLOMITES (KÜHWIESENKOPF/ MONTE PRÀ DELLA VACCA, BRAIES): A FIRST REPORT (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
The knowledge of Triassic macroflora from the Dolomites mostly concerns the Ladinian, while literature data on Anisian plants are scarce. This gap is filled by the discovery, reported here, of a rich plant deposit from Kühwiesenkopf / Monte Prà della Vacca (Prags/Braies Dolomites). The fossils occur in a horizon, about 1 m thick, from the lower part of the Dont Formation, a basinal unit mostly constituted by hemipelagic, terrigenous-carbonatic sediments of Pelsonian - Illyrian age. The stratigrafic interval with the plant horizon is Pelsonian in age. A preliminary systematic analysis of the numerous and well preserved specimens has allowed the identification of at least 17 genera. The taxa belong primarily to the Pteridophyta (Anomopteris, Neuropteridium, Cladophlebis, Crematopteris, ?Marattiopsis), subordinately to the Cycadophyta (Bjuvia, Taeniopteris, Dioonitocarpidium, Pterophyllum / Nilssonia). Coniferophyta are represented by Voltzia, ?Voltzia and Albertia; the latter genus is recorded herein for the first time in the Middle Triassic of the Dolomites. Besides, two Lycophyta genera (?Isoetites, Lycophyta new taxon), three Pteridospermae genera (?Sagenopteris, Scytophyllum and Peltaspermum), and one Sphenophyta genus (Equisetites) have also been recognized.